Institutions as game theory outcomes: Towards a cognitive-experimental inquiry - Angela Ambrosino (International Journal of Management, Economics and Social Sciences (IJMESS), 2013)
This paper investigates two different approaches to the analysis of institutions using game theory and discusses their methodological and theoretical implications for further research. Starting from von Neumann and Morgenstern's theory, we investigate, how Schotter and Schelling's approaches to the analysis of economic institutions contribute to develop a proper cognitive method to investigate institutions as the unplanned outcome of self- interested individual behavior? While the game theory model developed by Schotter does not allow to encompass the complexity of decision-making processes leading to the emergence of institutions, Schelling's empirical approach contributes to the cognitive inquiry into economic institutions and it opens the way to an interdisciplinary research method in which pure theory, empirical research and insight coming from different research fields work together. Starting form Schelling's work it is possible to draw the progress achieved by the cognitive economics of institutions and to suggest the need of further experimental and empirical research to better understand the cognitive dynamics that shape human behavior and influence the emergence of economic institutions.
Keywords: B25; B40; B53; C70; D02; E40; 330; institutions; game theory; cognition; Hayek; Schotter; Schelling